Thermodynamic Efficiency of Somatic Exocytosis of Serotonin - Noguez, Paula; Rubí, J. Miguel; De-Miguel, Francisco F. (Frontiers in Physiology, 2019)
Through somatic exocytosis neurons liberate immense amounts of transmitter molecules that modulate the functioning of the nervous system. A stream of action potentials triggers an ATP-dependent transport of transmitter-containing vesicles to the plasma membrane, that ends with a large-scale exocytosis. It is commonly assumed that biological processes use metabolic energy with a high thermodynamic efficiency, meaning that most energy generates work with minor dissipation. However, the intricate ultrastructure underlying the pathway for the vesicle flow necessary for somatic exocytosis challenges this possibility. To study this problem here we first applied thermodynamic theory to quantify the efficiency of somatic exocytosis of the vital transmitter serotonin. Then we correlated the efficiency to the ultrastructure of the transport pathway of the vesicles. Exocytosis was evoked in cultured Retzius neurons of the leech by trains of 10 impulses delivered at 20Hz. The kinetics of exocytosis was quantified from the gradual fluorescence increase of FM1-43 dye as it became incorporated into vesicles that underwent their exo-endocytosis cycle. By fitting a model of the vesicle transport carried by motor forces to the kinetics of exocytosis, we calculated the thermodynamic efficiency of the ATP expenses per vesicle, as the power of the transport divided by total energy produced by the hydrolysis of ATP during the process. The efficiency was remarkably low (0.1 - 6.4%) and the values formed a W-shape distribution with the transport distances of the vesicles. Electron micrographs and fluorescent staining of the actin cortex indicated that the slopes of the W chart could be explained by the interaction of vesicles with the actin cortex and the calcium-releasing endoplasmic reticulum. We showed that the application of thermodynamic permitted to predict aspects of the intracellular structure. Our results suggest that the distribution of subcellular structures that are essential for somatic exocytosis abates the thermodynamic efficiency of the transport by hampering vesicle mobilization. It is remarkable that the modulation of the nervous system occurs at the expenses of an efficient use of metabolic energy.